Butirosin, a New Aminoglycosidic Antibiotic Complex: Bacterial Origin and Some Microbiological Studies - Howells, John D. (1972)
Butirosin, a new aminoglycosidic antibiotic complex, was produced by submerged fermentation with each of two strains of Bacillus circulans. A paper-disc, agar-diffusion assay which employs Escherichia coli (P-D 04863) as the test organism has been developed. Shaken-flask and stirred-jar fermentations in a medium containing glycerol, soybean meal, meat peptone, ammonium chloride, and calcium carbonate reach titers of 500 to 700 μg of butirosin base per ml. Butirosin is active against several gram-positive and gram-negative bacteria including Pseudomonas aeruginosa.